(untitled) (Czech Journal of International Relations, 2001)
Enver Hasani: Dissolution of Yugoslavia and the case of Kosova. Political and legal aspects. 1st ed. Tirana: Albanian Institute for International Studies, 2000, 132 stran, ISBN 99927-659-0-9.